Influence of Dietary Supplementation of Probiotic Pediococcus acidilactici MA18/5M During the Transition From Freshwater to Seawater on Intestinal Health and Microbiota of Atlantic Salmon (Salmo salar L.) - Jaramillo-Torres, Alexander; Rawling, Mark D.; Rodiles, Ana; Mikalsen, Heidi E.; Johansen, Lill-Heidi; Tinsley, John; Forberg, Torunn; Aasum, Elisabeth; Castex, Mathieu; Merrifield, Daniel Lee (Frontiers in Microbiology, 2019)
The aim of this study was to assess the effect of the transfer from freshwater to seawater on the distal intestinal bacterial communities of Atlantic salmon (Salmo salar L.) and to evaluate the effect of dietary inclusion of Pediococcus.acidilactici MA18/5M. In this context, other aspects pertaining to fish health and antiviral response were also investigated. A 12-week feeding trial was conducted in a flow-through rearing system involving 6 weeks in freshwater and 6 weeks in seawater. Fish received one of two diets: control diet or probiotic diet. The composition of the salmon gut bacterial communities was determined by high-throughput sequencing of digesta and mucosa samples from both the freshwater and seawater stage. The main phyla detected during both freshwater and seawater stages were Firmicutes, Proteobacteria, Fusobacteria, and Actinobacteria. Significant differences were observed in the intestinal microbiota in the digesta and mucosa. Both probiotic supplementation and the seawater transfer had a substantial impact on the microbial communities, with most pronounced changes detected in the mucosal communities after seawater transfer. The probiotic-fed fish showed a significantly higher antiviral response (mx-1 and tlr3 gene expression) in the distal intestine. Feeding probiotics during the freshwater stage did not significantly increase survival after infectious pancreatic necrosis virus (IPNV) challenge after seawater transfer, although higher survival was observed in one out of two replicate challenge tanks.